2019
DOI: 10.1111/1440-1681.13205
|View full text |Cite
|
Sign up to set email alerts
|

miR‐138 mediates sorafenib‐induced cell survival and is associated with poor prognosis in cholangiocarcinoma cells

Abstract: Cholangiocarcinoma is an aggressive malignancy with rapid invasion, metastasis and poor prognosis, however, the mechanism mediating its cholangiocarcinoma development needs further investigation. Here, we demonstrate that decreased miR-138 in tumor tissues is related to the poor prognosis in patients, and that miR-138 mediates sorafenib-induced cell survival in cholangiocarcinoma cells. Moreover, miR-138 negatively regulates SOX4 expression by specifically targeting its 3′ untranslated region (3′ UTR). As per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Indeed, the prognostic values of SOX4 have previously been reported in some malignant tumors. Some experimental studies have revealed that SXO4 expression is correlated with poor prognosis in patients with tumors, such as CHOL [19] and LAML [20]. The prognostic value of SOX4 was partly validated again in our study, despite some controversial results.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the prognostic values of SOX4 have previously been reported in some malignant tumors. Some experimental studies have revealed that SXO4 expression is correlated with poor prognosis in patients with tumors, such as CHOL [19] and LAML [20]. The prognostic value of SOX4 was partly validated again in our study, despite some controversial results.…”
Section: Discussionsupporting
confidence: 64%
“…The analysis of miR-596 expression in real-time qRT-PCR assay was performed as previously described ( 18 , 19 ). Total RNA was extracted using the RNeasy Mini Kit (Qiagen) and real-time qRT-PCR was performed as previously reported ( 18 , 19 ). The primers for miRNAs were synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…SOX4 overexpression promotes cell proliferation in rectal cancer, non-small cell lung cancer and breast cancer (15)(16)(17). Recently, studies have indicated that miR-381, miR-138, miR-30a-5p, miR-211 and miR-30a-5p inhibit cell migration and invasion in human GC by down regulating SOX4 (18)(19)(20)(21). In this study, we identified low expression of miR-596 in GC by analyzing three GC miRNA microarray datasets, and serum from GC patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, miR-138 is a significant contributor to overcoming sorafenib resistance in CCA by modulation of tumor stemness. It targets the transcription factor Sex-determining region Y-related (SRY) high-mobility group box 4 (SOX4), which regulates tumor growth, metastasis, and stemness [ 69 , 72 ]. Downregulation of miR-138 is associated with increased proliferation, migration, and invasion in CCA [ 73 ].…”
Section: Mirna and Drug Resistancementioning
confidence: 99%